Comparatieve theologie: De noodzaak tot religieuze meertaligheid - Hintersteiner, Norbert (Tijdschrift voor theologie, 2007)
This article examines a few of the questions and propositions found in recent comparative theology. The author first situates comparative theology at the intersection of cross-cultural and interfaith translation. The hypothesis developed in this article is that theology has always been, and still is, an intrinsically comparative discipline. Then, a few contemporary definitions are used to explain what comparative theology is today. Third, the author analyses Francis Clooney’s pioneering work in modern comparative theology. This focus includes attention for several systematic elements considered an essential part of this theology. Finally, he develops a heuristically and epistemologically instructive access to the discourse and practice of comparative theology by illuminating the issue of the degree to which traditions can be translated.